Utilization of live feeds in fish larviculture: A review - Teye-Gaga, Christoher; Molnár, Péter István; Mohammed, Elshafia Ali Hamid; Bársony, Péter (Acta Agraria Debreceniensis, 2025)
This review examines the significance of live feeds in commercial aquaculture industry for production of fish and shrimp larvae, along with various challenges and prospects. Live feeds are an essential food source in larviculture, especially for marine fish, which depend on them for nutrition during the initial days of exogenous feeding. They are palatable, highly digestible, and their movement stimulates natural hunting and foraging instincts, promoting better development, lowering captivity stress, and increasing survival rates. Artemia is the most commonly used live feed in larviculture; however, it has low levels of omega-3 HUFA. Copepods are the most nutritionally rich live feed, containing high levels of DHA and EPA. Despite these benefits, they are less frequently used in larviculture due to technical challenges associated with large-scale cultivation at high densities. The use of live feed is labour-intensive and costly. The feeding period for fish larvae can be shortened using a co-feeding strategy. Microalgae rich in DHA have been utilized to enrich live feeds. Further research is needed to determine the most effective approach to significantly reduce the weaning time of fish larvae from live feed. This will lead to gradual and eventual complete replacement of life feed in the near future.